Controllable Electrochemical Synthesis and Photovoltaic Performance of Bismuth Oxide/Graphene Oxide Nanostructure Arrays - Fatma Bayrakçeken Nişancı (Journal of Advanced Research in Natural and Applied Sciences)
The electrodeposition coated graphene oxide (GO) sheets on semiconductor metal oxide substrates are reduced to produce transparent, flexible, and conductive electrodes. Electrochemically produced bismuth oxide nanoflower films with high crystallinity were characterized by depositing reduced graphene oxide (GO) films on top. The influence of coating period on the shape, structure, and characteristics of electrochemically formed metal oxides was also examined. The graphene oxide modified metal oxide electrode was successfully manufactured using an electrochemical method and characterized using potential controlled electrochemical deposition, atomic force microscopy, scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction techniques, and Raman measurements. By controlling the deposition period, we can regulate the form and size of electroprecipita-ted bismuth oxide/graphene oxide nanostructures using this electrochemical method from aqueous bismuth oxi-de/graphene oxide suspensions. The nanostructured bismuth oxide/graphene oxide electrode that results has high photovoltaic characteristics and can be employed in solar energy conversion applications. Our findings suggest that indium tin oxide (ITO) or bismuth oxide-GO films on gold electrodes may be used to enhance surface area in electrochemical synthesis, and that it is conceivable to synthesize semiconductor metal oxides in GO films for future flexible photovoltaic applications.